Comparative Photocatalytic Degradation of Alizarin Red S Dye using Cobalt-Doped TiO2 under UV, Visible and Solar Light Irradiation - Gupta, Nikita S.; Mandavgane, Susmita A. (Asian Journal of Chemistry, 2026)
Titanium dioxide (TiO2) is a widely studied photocatalyst, although its broad band gap restricts its response mainly to the ultraviolet region. This study investigates the effect of cobalt doping on the optical properties and photocatalytic activity of TiO2 under ultraviolet (UV), visible and solar irradiation. Co-doped TiO2 containing 0.5 mol% Co was synthesized by the sol–gel method. The crystal structure, morphology, particle size and elemental composition were examined by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), selected-area electron diffraction (SAED) and energy-dispersive X-ray spectroscopy (EDX). Optical absorption characteristics were evaluated by UV-visible diffuse reflectance spectroscopy (DRS) and the band gap energy was estimated from Tauc plots. The photocatalytic activity of the materials was evaluated using Alizarin dye as a model pollutant under UV, visible and solar irradiation, with the degradation kinetics analyzed using a pseudo-first-order model. XRD analysis confirmed the formation of highly crystalline, single-phase anatase TiO2. TEM images revealed nearly spherical nanoparticles with particle sizes of approximately 30-40 nm, while SAED patterns were consistent with the crystalline anatase structure. EDX analysis confirmed the presence of Co and TiO2 constituents without detectable extraneous elements. Co doping reduced the optical band gap from 3.2 eV for pristine TiO2 to 2.0 eV for Co-doped TiO2, extending the light absorption toward the visible region. After 60 min of irradiation, Alizarin red S (ARS) degradation reached 73.53%, 48.44% and 63.46% under UV, visible and solar light, respectively, with corresponding pseudo-first-order rate constants of 0.01819, 0.01073 and 0.01608 min–1. The reduced band gap and enhanced reaction kinetics under visible and solar irradiation establish Co-doped TiO2 as an effective photocatalyst for light-assisted wastewater treatment.